Fellowships for African researchers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The Project on African Agriculture: Crisis and Transformation is offering fellowships to African researchers or to research teams working alongside them for innovative projects that combine both training and research activities. Interdisciplinary...